Efektivitas Myofascial Release dan Muscle Energy Technique Terhadap Kualitas Hidup Pasien Tension Type Headache - Raisa Zukhrufa, Hana; Santoso, Iman (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Tension Type Headache (TTH) is a common health problem that has a significant impact on an individual's quality of life. Various physical therapies have been used to treat TTH symptoms, including Myofascial Release (MFR) and Muscle Energy Technique (MET). However, stronger evidence is still needed on the effectiveness of combining these two techniques in reducing the intensity of pain and improving the quality of life of TTH patients. The research aims to analyse the effectiveness of a combination of MFR and MET techniques on reducing pain intensity, increasing cervical range of motion, and improving the quality of life of TTH patients. This study used a systematic review method with a PRISMA-P approach and a PICOS framework. The research sample consisted of articles published between 2020 and 2025, which were identified through searches in the PubMed, Crossref, and Web of Science databases. Data analysis was conducted descriptively based on the results found in relevant studies.The results showed that the intervention of MFR and MET significantly reduced pain intensity, increased cervical range of motion, and improved the quality of life of TTH patients. The study shows that the combination of MFR and MET techniques is effective in managing TTH symptoms and can improve the patient's quality of life. These results provide a basis for non-pharmacological physical therapy in the management of TTH.